The principles of the treatment of patients with external ear inflammatory diseases - V. M. Svistushkin; H. G. Varosyan (Медицинский совет, 2018)
The article reflects the issues of the management of patients with external ear inflammatory diseases. Authors describe the pathogenetic and etiological factors of this pathology development. In the article the principles of conservative treatment and the possibility of using measures that prevent relapses are described, depending on the severity and nature of the pathological process. The paper consists a brief review of clinical studies on the effectiveness of a complex drug with antibacterial, antiinflammatory and antiedematous action based on neomycin, polymyxin B and dexamethasone is reviewed.